Modos de comunicação e aprendizagem de línguas no século XXI: desafios na internacionalização - Concário, Marcelo [UNESP]; Nóbrega, Maria Helena Da; Ramos, Joaquim Coelho (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2020)
Multicultural and multilingual issues are of central importance in everyday communication as a result of growing internationalization. Thus, as the places and possibilities for the authorized use of (first and foreign) languages become research objects and relevant topics in teacher education, conventions of use and diversity reaffirm their importance in communicative processes, and linguistic-communicative skills consolidate their value as inalienable assets in professional qualification. This paper addresses the complexity of this new scenario and how language learning relates to new ways of knowing something, knowing how to (learn to) do something, and knowing how to exist. It consists in an exploratory endeavor, based on the authors’ experience as teachers, researchers and managers, which has been motivated by reflections on our individual presentations in the VII World Symposium on Portuguese Language Studies (VII Simpósio Mundial de Estudos da Língua Portuguesa), which took place in Porto de Galinhas (Brazil) in August 2019. The objective is to look into internationalization in three specific domains, i.e.: the modes of communication highlighted in The Common European Framework of Reference (CEFR), the teaching of languages for specific purposes, and education policies for the 21st century. Following the theoretical discussion, we attempt to demonstrate how the management of teaching policies related to internationalization - Portuguese to speakers of other languages, or other languages to speakers of Portuguese - can foster the development of practices in response to pressing professional and educational issues in the 21st century.

As questões multiculturais e multilinguísticas são elementos essenciais na comunicação cotidiana em decorrência da crescente internacionalização. Dessa forma, ao mesmo tempo em que os espaços e as possibilidades para o uso autorizado das línguas maternas e estrangeiras tornam-se objetos de pesquisa e temas relevantes para cursos de formação de professores, as convenções de uso e a diversidade reafirmam sua importância nos processos comunicativos, e as competências linguístico-comunicativas consolidam-se como ferramentas inalienáveis na formação profissional. Este artigo avalia a complexidade desses novos contextos e como a aprendizagem de línguas dialoga com novas formas de saber, saber fazer, saber ser e saber aprender. Trata-se de um estudo exploratório, baseado nas experiências dos autores com ensino, pesquisa e gestão, e decorrente das reflexões suscitadas por nossas apresentações individuais no VII Simpósio Mundial de Estudos da Língua Portuguesa, realizado em agosto de 2019 em Porto de Galinhas, Pernambuco. O objetivo é problematizar a internacionalização em três âmbitos específicos, a saber: nos modos de comunicação destacados no Quadro Comum Europeu; no ensino de língua para fins específicos e nas políticas educacionais para o século XXI. Ao final da abordagem teórica, discute-se como a gestão de projetos pedagógicos relacionados à internacionalização - português para falantes de outras línguas ou outras línguas para falantes de português - pode contribuir para promover práticas responsivas às questões profissionais e educacionais do século XXI.
Modes of communication and language learning in the 21st century: challenges for internationalization
Keywords: language education; internationalization; technology; ensino de línguas; internacionalização; tecnologia